2008
DOI: 10.1089/jpm.2007.0294
|View full text |Cite
|
Sign up to set email alerts
|

Legacy Activities as Interventions Approaching the End of Life

Abstract: We examined the efficacy of an innovative family-based intervention designed to decrease caregiving stress and increase family communication among individuals with chronic, life-limiting illnesses and their family caregivers in a randomized, contact control group design. The intervention group received three home visits in which the interventionist actively worked with the family to construct a personal Legacy, usually a scrap-book with photographs or audiotaped stories. Control group families received three s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 39 publications
1
102
0
Order By: Relevance
“…The positive nature of legacy-making is consistent with previous studies, which have shown patient benefits including decreased breathing difficulties, distraction from pain and negative thoughts, increased religious meaning, greater social interaction, leaving a legacy, preparation for end of life, greater appreciation for self, as well as improved family communication and decreased caregiver stress. [4][5][6][7][8] However, previous studies have focused on adult and elderly adult patients [4][5][6][7] and have rarely explored legacy-making specific to pediatric populations.…”
Section: Legacy-making Activities 575 Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive nature of legacy-making is consistent with previous studies, which have shown patient benefits including decreased breathing difficulties, distraction from pain and negative thoughts, increased religious meaning, greater social interaction, leaving a legacy, preparation for end of life, greater appreciation for self, as well as improved family communication and decreased caregiver stress. [4][5][6][7][8] However, previous studies have focused on adult and elderly adult patients [4][5][6][7] and have rarely explored legacy-making specific to pediatric populations.…”
Section: Legacy-making Activities 575 Resultsmentioning
confidence: 99%
“…3-8 Legacy-making activities including life review, dignity therapy, board games, or creative arts have been shown to benefit adult patients living with advanced cancer and their family members, [4][5][6][7][8] but have rarely been tested in pediatric populations. A qualitative study explored bereaved parents' and siblings' reports of legacies by children who had died of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Specifi c aims of reminiscence therapy include (a) enhancing communication, (b) increasing a sense of personal identity, (c) providing an enjoyable activity with others, (d) improving mood and well-being and quality of life, (e) stimulating memories, (f) increasing individualization of care, and (g) reducing caregiver strain (Moos & Bjorn, 2006;Pusey, 2000 ;Woods et al). Evidence supporting interpersonal benefi ts of reminiscence therapy includes enhanced caregiver -patient relation ship, en hanced socializing with others, enhanced feelings of well-being, and providing a family-shared legacy ( Allen, 2009, Allen, Hilgeman, Ege, Shuster, & Burgio, 2008Brooker & Duce, 2000 ;Gibson, 1994 ;Olsen, Hutchings, & Ehrenkrantz, 2000 ;Woods, 1994 ). Woods and colleagues suggest that further clinical studies are required on reminiscence therapy to understand its impacts.…”
Section: Dementia Stimulation Interventionsmentioning
confidence: 99%
“…There have been a few foundational studies of hospice psychosocial interventions. Results of these studies indicate positive clinical outcomes such as reduction of caregiver stress and anxiety, with increased problem-solving skills as well as quality of life (Allen et al, 2008;Carter, 2006;Csikai et al, 2013;Dimiris et al, 2010;Dimiris et al, 2012;Drossel et al, 2011;Empeño et al, 2011;Gordon, 2013;Keefe et al, 2005;Kilburn et al, 2011;Kruse et al, 2013;McMillan et al, 2006;McMillan et al, 2007;Moody, 2004;Northouse et al, 2007;Northouse et al, 2013;Ott & Lueger, 2002;& Steinhauser et al, 2009;Washington et al, 2012). However, comprehensive hospice psychosocial service delivery and consumer utilization remains understudied (Reese, 2013;Reese & Raymer, 2004).…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Currently, there are few psychosocial interventions that have been developed and tested specifically for the hospice population and none are specific to underserved hospice populations (Allen et al, 2008;Carter, 2006;Csikai et al, 2013); Drossel et al, 2011;Gordon, 2013;Keefe et al, 2005;Kruse, et al, 2013;McMillan et al, 2006;McMillan et al, 2007;Moody, 2004;Northouse et al, 2007;Northouse et al, 2013;Ott & Lueger, 2002, & Steinhauser et al, 2009 Dimiris et al, 2010;Dimiris et al, 2012;Washington et al, 2012). This intervention has shown to have significant practical effects when implemented, but actual dissemination and rigorous practice of the model in the field have yet to be evaluated .…”
Section: Implications For Social Work Research Policy Education Andmentioning
confidence: 99%